Prevalence of anxiety, depression and kinesiophobia in patients with low back pain and their association with the symptoms of low back spinal pain - Tathiana O. Trocoli; Ricardo V. Botelho (Revista Brasileira de Reumatologia)
ABSTRACT Objective: To evaluate the prevalence of anxiety, depression and kinesiophobia and their association with the symptoms of low back pain. Methods: A total of 65 patients were divided into three groups: Organic, Amplified Organic and Non-Organic. They answered the Beck Anxiety Inventory, Beck Depression Inventory and Tampa Scale of Kinesiophobia and were evaluated according to their pain level using the Visual Analogic Scale. Results: The average kinesiophobia scores of the patients in the Organic, Amplified Organic and Non-Organic groups were 36.26, 36.21 and 23.06 points, respectively. Patients who were classified into the Organic group experienced the most kinesiophobia out of all three groups (p = 0.007). The average anxiety scores of the patients in the Organic, Amplified Organic and Non-Organic groups were 33.17, 32.79 and 32.81 points, respectively, with no significant difference among the groups (p = 0.99). The average depression scores of the patients in the Organic, Amplified Organic and Non-Organic groups were 32.54, 28.79 and 37.69 points, respectively, with no significant difference among the groups (p = 0.29). Conclusion: There was no association between the groups and anxiety and depression. However, there was a positive correlation between kinesiophobia and the Organic group. Studies of other patient samples are needed to confirm the reproducibility and validity of these data in other populations.